2021
DOI: 10.1186/s13148-021-01095-5
|View full text |Cite
|
Sign up to set email alerts
|

Methylated circulating tumor DNA as a biomarker for colorectal cancer diagnosis, prognosis, and prediction

Abstract: Worldwide, colorectal cancer (CRC) is a deadly disease whose death rate ranks second among cancers though its incidence ranks third. Early CRC detection is key and is associated with improved survival outcomes. However, existing tests for CRC diagnosis have several weaknesses thus rendering them inefficient. Moreover, reliable prognostic tests that can predict the overall cancer outcome and recurrence of the disease as well as predictive markers that can assess effectiveness of therapy are still lacking. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 121 publications
(194 reference statements)
1
34
0
Order By: Relevance
“…However, the PNI status can be only determined after surgical dissection of tumor tissue, limiting its practical use in LNM prediction, and the preoperative non-invasive examinations are more attractive to clinicians to make personalized treatment. Preoperative blood tests are promising tools to predict survival and LNM in patients with malignant tumors such as colorectal cancer [ 37 ], renal cell cancer [ 38 ] and OSCC [ 39 ]. We found that preoperative plasma CGRP levels were predictive of LNM, yielding an AUC value of 0.8088.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PNI status can be only determined after surgical dissection of tumor tissue, limiting its practical use in LNM prediction, and the preoperative non-invasive examinations are more attractive to clinicians to make personalized treatment. Preoperative blood tests are promising tools to predict survival and LNM in patients with malignant tumors such as colorectal cancer [ 37 ], renal cell cancer [ 38 ] and OSCC [ 39 ]. We found that preoperative plasma CGRP levels were predictive of LNM, yielding an AUC value of 0.8088.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing with glioblastoma, nearly all IDH-mutant gliomas manifest a positive CpG island methylator phenotype (G-CIMP+), linking this DNA methylation status to a favorable prognosis [120]. In addition, and similar to the wellknown ColoPrint and MammaPrint gene expression-based CRC and breast cancer classifiers [121,122], several epigenetic DNA methylation-based signatures show promising clinical results, as in the classification of cancers of unknown primary using bulk-based DNA methylation arrays [123] or in the early detection of blood-circulating tumor cells from patients with CRC, breast or prostate cancer [44,124,125]. Even though these bulk-based epigenetic clinical approaches are useful, their major drawback lies in the unsolved tumor heterogeneity.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
“…A recent key advancement in ctDNA technology is the detection of epigenetic aberrations, specifically methylation signatures, in blood-derived ctDNA from patients with solid tumors [64][65][66]. DNA methylation is an epigenetic modification in which a methyl group (-CH 3 ) is added to position 5 of the DNA cytosine ring by DNA methyltransferases, leading to reduced gene expression [67]. In carcinogenesis, the DNA methylation of promoter sites, specifically CpG islands, of tumor suppressor genes is a common early event and ctDNA methylation profiling can be harnessed as a key tool for cancer detection [66].…”
Section: History Of Cfdnamentioning
confidence: 99%